Food security: innovative aspect - V. S. Balabanov; M. N. Dudin; N. V. Ljasnikov (Путеводитель предпринимателя, 2020)
In article single questions of ensuring food security are considered, including questions of providing the population are investigated by good-quality, available and harmless foodstuff and resources. The special attention is paid to the prospects of innovative development of the agro-industrial sphere, as one of the key sectors occupied information of due level of nationalfood security.